Fossil Genera in Elateridae (Insecta, Coleoptera): A Triassic Origin and Jurassic Diversification - Robin Kundrata; Gabriela Packova; Johana Hoffmannova (Insects, 2020)
Insect fossils bear important information about the evolutionary history of the group. The fossil record of Elateridae, a large cosmopolitan beetle family, has been greatly understudied and the available data are often replete with ambiguity and uncertainty. The research of Elateridae evolution cannot be done without solid genus-group name concepts. In this study we provide an updated comprehensive summary of the fossil genera in Elateridae, including their systematic placement and information on the type species, gender, number of species, age range, and relevant bibliography. We list seven valid fossil genera in Agrypninae, one in Cardiophorinae, two in Dendrometrinae, five in Elaterinae, two in Negastriinae, one in Omalisinae, one in Pityobiinae, and 36 in Protagrypninae. Additional 19 genera are tentatively classified as Elateridae incertae sedis, and their placements are discussed. Further, we move genera Babuskaya Martins-Neto & Gallego, 2009, Cardiosyne Martins-Neto & Gallego, 2006, Fengningia Hong, 1984 and Gemelina Martins-Neto & Gallego, 2006 from Elateridae to Coleoptera incertae sedis. We also discuss the genera previously placed in Elateridae, which are currently not included in the family. The data on the fossil generic diversity suggest that Elateridae originated in the Triassic and rapidly diversified and became comparatively abundant through the Jurassic. We call for further research on the fossil Elateridae from various deposits in order to increase our knowledge on the origin, evolution, and palaeodiversity of the group.